Genome-wide identification and characterization of pectin methylesterase inhibitor gene family members related to abiotic stresses in watermelon - Zhang, Siyu; Yuan, Xinhao; Duan, Jiahao; Hu, Jun; Wei, Chunhua; Zhang, Yong; Wang, Jiafa; Li, Chao; Hou, Shengcan; Luo, Xiaodan; Li, Junhua; Zhang, Xian; et al. (Frontiers in Plant Science, 2024)
Pectin is a vital component of the plant cell walls and its methylation process is regulated by pectin methylesterase inhibitor (PMEI). PMEI regulates the structural and functional modifications of cell walls in plant and plays an important role in plant processes such as seed germination, fruit ripening, and stress response. While the PMEI gene family has been well characterized in model plants, the understanding of the molecular evolution and biological functions of the PMEI gene family in watermelon remains limited. In this study, 60 ClPMEI genes were identified and characterized, revealing their dispersion on multiple chromosomes. Based on a systematic developmental analysis, these genes were classified into three subfamilies, which was further supported by the exons, introns, and conserved motifs distribution. Analysis of cis-elements and expression patterns indicated that ClPMEIs might be involved in regulating the tolerance of watermelon to various abiotic stresses.Moreover, distinct ClPMEI genes exhibit specific functions under different abiotic stresses. For excample. ClPMEI51 and ClPMEI54 showed a significant up-regulation in expression levels during the late stage of drought treatments, while ClPMEI3 and ClPMEI12 displayed a significant downregulation under low temperature induction. Subcellular localization prediction and analysis revealed that the ClPMEI family member proteins were localized to the cell membrane. This study provided an important foundation for further exploring the functions of ClPMEI genes in watermelon.